Pembelajaran Pendidikan Agama Islam pada Anak Melalui Metode Bercerita di Yayasan Pendidikan Al-Fazwa Islamic School - Hanum, Latifah (Fitrah: Journal of Islamic Education, 2022)
This study aims to analyze the application of the storytelling method, its success, and obstacles in instilling religious education in preschool-aged children at the Al-Fazwa Islamic School Education Foundation, Sidodadi Village. This research uses the classroom action research method which consists of two cycles. The results showed that the achievement of children's moral development and religious values ​​in the pre-cycle there were 6 children (40%) in the category of undeveloped abilities, and 3 children (20%) in the category of ability to begin to develop, and 6 children (40%) in the category of ability. develop as expected. In the first cycle, there were 3 (20%) in the category of undeveloped ability, 3 children (20%), in the category of ability to begin to develop, and 9 children (60%) in the category of ability to develop as expected. In cycle II, there were 3 children (20%) in the category of ability to begin to develop and 12 children (18%) in the category of developing as expected. The obstacles faced are the lack of teaching aid facilities, the low ability of teachers, the difficulty of packaging abstract material into concrete, and the lack of parental support.